Screening for new brewing yeasts in the non-Saccharomyces sector with Torulaspora delbrueckii as model - Michel, Maximilian; Kopecká, Jana; Meier-Dörnberg, Tim; Zarnkow, Martin; Jacob, Fritz; Hutzler, Mathias (Yeast, 2016)
This study describes a screening system for future brewing yeasts focusing on non-Saccharomyces yeasts. The aim was to find new yeast strains that can ferment beer wort into a respectable beer. Ten Torulaspora delbrueckii strains were put through the screening system, which included sugar utilization tests, hop resistance tests, ethanol resistance tests, polymerase chain reaction fingerprinting, propagation tests, amino acid catabolism and anabolism, phenolic off-flavour tests and trial fermentations. Trial fermentations were analysed for extract reduction, pH drop, yeast concentration in bulk fluid and fermentation by-products. All investigated strains were able to partly ferment wort sugars and showed high tolerance to hop compounds and ethanol. One of the investigated yeast strains fermented all the wort sugars and produced a respectable fruity flavour and a beer of average ethanol content with a high volatile flavour compound concentration. Two other strains could possibly be used for pre-fermentation as a bio-flavouring agent for beers that have been post-fermented by Saccharomyces strains as a consequence of their low sugar utilization but good flavour-forming properties.
Keywords: Odorants; biologické modely; pivo; Hydrogen-Ion Concentration; teplota; technika náhodné amplifikace polymorfní DNA; DNA Fingerprinting; Torulaspora; Models, Biological; DNA, Fungal; fermentace; chuť; odoranty; DNA fingerprinting; Temperature; Beer; metabolismus sacharidů; Random Amplified Polymorphic DNA Technique; Fermentation; Taste; DNA fungální; Amino Acids; aminokyseliny; Carbohydrate Metabolism; koncentrace vodíkových iontů; kvantitativní polymerázová řetězová reakce; Real-Time Polymerase Chain Reaction